The Impact of Immunity on Developing Literacy Culture at Primary School: Investigating Students’ Extroverted and Introverted Personalities - Evi Fatimatur Rusydiyah; Misbakhul Munir; Hernik Farisia; Hanik Faizah; Risa Purnamasari (Journal of Innovation in Educational and Cultural Research, 2023)
The development of literary culture in schools needs a literate ecosystem and full support from literacy activists in schools. This study aims to describe and explore the profile of literacy activists in madrasahs in terms of their level of immunity and personality traits. This study investigates the effect of student immunity as literacy activists in madrasahs with extroverted and introverted personality types on the ability to develop a literary culture. The parameters used to investigate the immunity levels in extroverted and introverted students were by examining the number of leukocytes, types of leukocytes, and the results of the IL-6 examination using the ELISA method. The results show that extroverted students have higher immunity than introverted students. The average leukocyte level of extroverted students is 24,350 cells/mm3 and introverted students is 50 cells/mm3. Meanwhile, the results of the IL-6 examination show the highest is 163,863 and the lowest is 43,984. Extroverted students can design various literacy programs that are challenging for students and are better able to build networks in developing literacy programs compared to introverted students. So, it can be concluded that extroverted students have a higher level of immunity, and also have the ability to explore and develop literacy programs better than introverted students.